Development and experimental investigation of smart antennas for unmanned aerial vehicles - Sugak, M. I.; Ballandovich, S. V.; Terentieva, P. V.; Kostikov, G. A. (2016 ElConRusNW : proceedings of the 2016 IEEE North West Russia Section Young Researchers in Electrical and Electronic Engineering Conference : February 2-3, 2016, St. Petersburg Russia, 2016)
Described are the designing and manufacturing azimuth-plane controlled radiation pattern for antenna arrays. Antennas characteristic dependences on geometry parameters obtained as well as control circuit parameters are given. The higher gain and noise immunity of the antenna array designed in comparison with common single antennas are shown.